Revenge of the stormbringer - Tremayne, Peter (Tremayne, Peter. Sister Fidelma novels, 2023)
Summer, AD 672. Princess Gelgeis has arrived in Cashel with her personal bodyguard, a troop of female warriors called the Daughters of the Storm. When one of them is found slain next to the sleeping chamber of the newly married king and queen and, a short time later, the stewardess of the royal house is poisoned, questions are raised as to everyone's safety. Fidelma and Eadulf must first explain the 'locked room' mystery of how the attack took place in King Colgu's specially built secure apartment. Then they must interrogate the growing list of suspects - even Enda, the commander of the household guard, who had formed a romantic attachment to the murdered attendant, cannot be ignored. As the fair being held to celebrate the king and queen's wedding approaches, tensions mount and Fidelma must work quickly to expose a ruthless killer before it is too late.